2020
DOI: 10.1080/14686996.2020.1820845
|View full text |Cite
|
Sign up to set email alerts
|

Conducting polymer-inorganic nanocomposite-based gas sensors: a review

Abstract: With the rapid development of conductive polymers, they have shown great potential in room-temperature chemical gas detection, as their electrical conductivity can be changed upon exposure to oxidative or reductive gas molecules at room temperature. However, due to their relatively low conductivity and high affinity toward volatile organic compounds and water molecules, they always exhibit low sensitivity, poor stability, and gas selectivity, which hinder their practical gas sensor applications. In addition, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(42 citation statements)
references
References 119 publications
(169 reference statements)
0
42
0
Order By: Relevance
“…Such sensors are important for a number of applications with particular attention being given to soft, wearable sensors which can monitor vital signs such as pulse and breathing. [1] In recent years nanocomposites, [2] generally consisting of 1D or 2D nanomaterials embedded in polymer matrices, have proven to be versatile materials and have been utilised in a number of end applications such as gas [3], chemical [4], thermal [5] and biological [6] sensing. In addition to this, polymer nanocomposites have been heavily studied as strain sensors [7,8,9].…”
mentioning
confidence: 99%
“…Such sensors are important for a number of applications with particular attention being given to soft, wearable sensors which can monitor vital signs such as pulse and breathing. [1] In recent years nanocomposites, [2] generally consisting of 1D or 2D nanomaterials embedded in polymer matrices, have proven to be versatile materials and have been utilised in a number of end applications such as gas [3], chemical [4], thermal [5] and biological [6] sensing. In addition to this, polymer nanocomposites have been heavily studied as strain sensors [7,8,9].…”
mentioning
confidence: 99%
“…As a result, it can be seen that the prepared nano composites have high sensitivity with short response times comparing to the pure polymer, proving that the introducing of metal oxides into the polymer matrix improve its conductivity properties [49]. This result confirmed that the sensors responded quickly to both the induction and removal of the H2S gas.…”
Section: Resultsmentioning
confidence: 53%
“…This charge transfer is generally transduced in conductivity changes that enable the gas/vapor detection even at room temperature, circumventing the need for thermal activation as in MOXs. Conductive polymers such as polypyrrole (PPy), polyaniline (PANI), polythiophene (PTh), and poly(3,4-ethylenedioxythiophene) (PEDOT), and their modifications with metals have been the most studied candidates for sensing VOCs [ 4 , 7 ] ( Figure 1 a). These materials demonstrated mostly resistive responses to vapors such as ethanol, methanol, and acetone, and gases such as NH 3 , NO 2 , and CO [ 5 ].…”
Section: Gas/vapor Sensitive Materialsmentioning
confidence: 99%
“…The sensing properties of these materials generally depend on the chemisorption of negatively charged oxygen adsorbates (O −2 , O − , and O 2− ) in air, which, due to charge transfer between the material and the analytes, change the electron density on the material surface. They may also depend on the chemical reaction between the sensitive material and the analyte, or the diffusion of species into the bulk of the material [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%